Scales vision. Readings for the virtual collection of images archivovisual.cl - Dobbs, Amarí Peliowski (2012)
A corpus of objects placed in the context of his statement, inspires acts of catalog, classify, structure. In this paper we present and analyze both theoretically, through the qualifying transaction, the digital file Visual Archive of Santiago. First, we will describe the process of formation and characteristics of this file to understand the motivations and the structure of it and, secondly, propose certain readings of this collection while allowing studying urban iconography. Offer readings iconographic system allows one hand, comprise a collection of images of a city as a source of historical research of the city, and on the other, opening possibilities for theoretical analysis, we believe, contribute to enriching the urban planning concrete work both projection and modeling of the city. We propose and analyze this file as an intangible heritage positioning (documents) in the service of the tangible (the city).